Laparoscopic greater curvature plication in morbidly obese women with type 2 diabetes: effects on glucose homeostasis, postprandial triglyceridemia and selected gut hormones - Bradnova, Olga; Kyrou, Ioannis; Hainer, Vojtech; Vcelak, Josef; Halkova, Tereza; Sramkova, Petra; Dolezalova, Karin; Fried, Martin; McTernan, Philip; Kumar, Sudhesh; Hill, Martin; Kunesova, Marie; et al. (Obesity surgery, 2014)
BACKGROUND: Laparoscopic greater curvature plication (LGCP) is an emerging bariatric procedure that reduces the gastric volume without implantable devices or gastrectomy. The aim of this study was to explore changes in glucose homeostasis, postprandial triglyceridemia, and meal-stimulated secretion of selected gut hormones [glucose-dependent insulinotropic polypeptide (GIP), glucagon-like peptide-1 (GLP-1), ghrelin, and obestatin] in patients with type 2 diabetes mellitus (T2DM) at 1 and 6 months after the procedure. METHODS: Thirteen morbidly obese T2DM women (mean age, 53.2 ± 8.76 years; body mass index, 40.1 ± 4.59 kg/m2) were prospectively investigated before the LGCP and at 1- and 6-month follow-up. At these time points, all study patients underwent a standardized liquid mixed-meal test, and blood was sampled for assessment of plasma levels of glucose, insulin, C-peptide, triglycerides, GIP, GLP-1, ghrelin, and obestatin. RESULTS: All patients had significant weight loss both at 1 and 6 months after the LGCP (p ≤ 0.002), with mean percent excess weight loss (%EWL) reaching 29.7 ± 2.9% at the 6-month follow-up. Fasting hyperglycemia and hyperinsulinemia improved significantly at 6 months after the LGCP (p < 0.05), with parallel improvement in insulin sensitivity and HbA1c levels (p < 0.0001). Meal-induced glucose plasma levels were significantly lower at 6 months after the LGCP (p < 0.0001), and postprandial triglyceridemia was also ameliorated at the 6-month follow-up (p < 0.001). Postprandial GIP plasma levels were significantly increased both at 1 and 6 months after the LGCP (p < 0.0001), whereas the overall meal-induced GLP-1 response was not significantly changed after the procedure (p > 0.05). Postprandial ghrelin plasma levels decreased at 1 and 6 months after the LGCP (p < 0.0001) with no significant changes in circulating obestatin levels. CONCLUSION: During the initial 6-month postoperative period, LGCP induces significant weight loss and improves the metabolic profile of morbidly obese T2DM patients, while it also decreases circulating postprandial ghrelin levels and increases the meal-induced GIP response.
Keywords: následné studie; žaludeční inhibiční polypeptid; lidé; Gastroplasty; laparoskopie; výsledek terapie; krevní glukóza; homeostáza; Gastrointestinal Hormones; Middle Aged; gastrointestinální hormony; Female; Body Mass Index; Glucagon-Like Peptide 1; Humans; Follow-Up Studies; index tělesné hmotnosti; Obesity, Morbid; gastroplastika; Triglycerides; lidé středního věku; diabetes mellitus 2. typu; Diabetes Mellitus, Type 2; hmotnostní úbytek; Ghrelin; Blood Glucose; Weight Loss; postprandiální období; Time Factors; ženské pohlaví; ghrelin; morbidní obezita; Postprandial Period; časové faktory; Treatment Outcome; Gastric Inhibitory Polypeptide; triglyceridy; Homeostasis; Laparoscopy; glukagonu podobný peptid 1